The Moxibustion-Induced Thermal Transport Effect Between the Heart and Lung Meridians With Infrared Thermography - Li, Xiaoyu; Jiang, Yongliang; Hu, Hantong; Lou, Jiali; Zhang, Yajun; He, Xiaofen; Wu, Yuanyuan; Fang, Junfan; Shao, Xiaomei; Fang, Jianqiao (Frontiers in Cardiovascular Medicine, 2022)
Objectives By comparing the differences in the thermal transport effect between the heart and lung meridians induced by moxibustion, this study aimed to investigate the specificity of site-to-site associations on the body surface between different meridians. Methods Eighty healthy participants were divided into the heart meridian intervention group and the lung meridian intervention group; moxibustion was performed at these two meridians, respectively. Baseline temperature and its change magnitude from baseline induced by moxibustion in 6 measuring sites of the heart and lung meridians were assessed by infrared thermography (IRT). Measuring sites included: Site 1 (Chize, LU5), Site 2 (midpoint of LU9 and LU5), Site 3 (Taiyuan, LU9), Site 4 (Shaohai, HT3), Site 5 (midpoint of HT7 and HT3), and Site 6 (Shenmen, HT7). Results Forty participants (20 male and 20 female, 27.90 ± 0.52 years) were assigned to the heart meridian intervention group, and 40 participants (20 male and 20 female, 28.08 ± 0.54 years) were assigned to the lung meridian intervention group. In the lung meridian intervention group (moxibustion over LU5), the temperature of the distal sites in the lung meridian increased significantly at 5, 10, and 15 min compared with pre-moxibustion (P < 0.001). The temperature of Site 4 in the heart meridian, which was nearest to the moxibustion site, increased significantly compared with pre-moxibustion (P < 0.05), while the temperature in the distal sites of the heart meridian did not differ significantly during moxibustion. Regarding the comparison of temperature change magnitude from baseline (ΔT) between the two meridians, the ΔT of Site 2 in the lung meridian was significantly higher than Site 4 in the heart meridian at 5 and 10 min after moxibustion (P < 0.05), despite that Site 2 was more distal from the moxibustion site than Site 4. Similarly, the ΔT of Site 3 in the lung meridian was significantly higher than Site 5 and Site 6 in the heart meridian at 5, 10, and 15 min after moxibustion (P < 0.05). In the heart meridian invervention group, similar thermal transport effect between the two meridians was observed. The thermal transport effect of the distal sites along the heart meridian was more significant than that of the site closer to the moxibustion site but located in the lung meridian. Taken together, aforementioned results indicated that the moxibustion-induced thermal transport effect between the heart and lung meridians is generally more significant in the distal sites along the corresponding meridian than that in the closer sites of the other meridian. Conclusions In the heart and lung meridians, the moxibustion-induced thermal transport effect is closely related to meridian routes, not just related to the absolute distance from the moxibustion site, thereby confirming the relative specificity of “site-to-site” associations on the body surface in these two meridians. Systematic Review Registration https://clinicaltrials.gov/ct2/show/NCT05330403, identifier NCT05330403.